Giant elastic-wave asymmetry in a linear passive circulator - Yabin Hu; Yongbo Li; Yongquan Liu; Bing Li; Johan Christensen (Nature Communications)
Abstract Nonreciprocal transmission of waves is highly desirable for the transport and redistribution of energy. However, building an asymmetric system to break time-reversal symmetry is relatively difficult because it tends to work under stringent guidelines, narrow bandwidth, or external impetus, particularly in a three-port system. Without breaking reciprocity, realizing “one-way” transmission of elastic waves by a linear and passive structure in a higher-dimensional asymmetric system, such as a three-port circulator, poses quite a challenge. Here, based on the wave-vector modulation mechanism, we propose an elastic-wave circulator that achieves this without breaking reciprocity, enabling perfect mode transition and wave trapping simultaneously. Requiring neither activated media nor relying on the nonlinearity of nonreciprocal devices, the circulator routes elastic waves purely in a clockwise direction, offering superior performance in broad bandwidth, robust behavior, and simple configuration. Our study provides a feasible platform for asymmetric wave transport in a three-port system, which can be useful in the routing, isolation, and harvesting of energy and can also be extended to other fields, such as electromagnetic and acoustic waves.